Critical illness?related corticosteroid insufficiency in children: A single center, prospective, cohort study - Patki, Vinayak K; Antin, Jennifer V; Agrawal, Sanket D (Indian Journal of Child Health, 2016)
Background: Although guidelines for diagnosis and management of critical illness?related corticosteroid insufficiency (CIRCI) in adults are developed, there is a paucity of data on CIRCI in children. Objective: To study the incidence, risk factors, mechanism, and associations of CIRCI in children using adrenocorticotropic hormone (ACTH) stimulation test. Materials and Methods: Single?center prospective cohort study was conducted in eight bedded pediatric intensive care unit of teaching hospital over a period of 1 year. Serum total cortisol concentration was measured in 110 critically ill children before and after stimulation with 250 ?g ACTH. CIRCI was defined by post?ACTH increment in serum cortisol ?9 ?g/dl. Children with and without CIRCI were compared. Results: Incidence of CIRCI was 38.2%. Children with CIRCI had higher median age (34 vs. 18 months), higher pediatric risk of mortality score (17.79±2.60 vs. 16.37±3.68), and significantly higher basal cortisol levels (27.37±11.64 vs. 22.02±7.26) (p=0.004) than those without CIRCI. There was a significantly higher (p=0.000) requirement of catecholamines (2.71±0.457 vs. 2.00±0.792) and higher additional fluid boluses (15.79±4.7 vs. 10.65±4.60) in children with CIRCI. However, duration of catecholamine use was not significantly different between two groups. The presence of CIRCI was not found to be an independent risk factor for mortality. For each additional use of catecholamine, the risk of CIRCI increased to 5.6 times; and for each extra fluid bolus, the risk increased to 1.2 times. Conclusion: CIRCI occurs in a wide spectrum of diseases in critically ill children associated with increased need for catecholamine and fluids. CIRCI is likely to be multifactorial in etiology and associated with high basal cortisol levels.